2012
DOI: 10.1021/ja3024737
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescence Light-Up Ag Nanocluster Probe That Discriminates Single-Nucleotide Variants by Emission Color

Abstract: Rapid and precise screening of small genetic variations, such as single-nucleotide polymorphisms (SNPs), among an individual’s genome is still an unmet challenge at point-of-care settings. One crucial step towards this goal is the development of discrimination probes that require no enzymatic reaction and are easy to use. Here we report a new type of fluorescent molecular probe, termed a chameleon NanoCluster Beacon (cNCB), that lights up into different colors upon binding SNP targets. NanoCluster Beacons (NCB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
215
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(219 citation statements)
references
References 48 publications
(151 reference statements)
1
215
0
Order By: Relevance
“…In a follow-up work, the authors further optimized the DNA sequences and demonstrated that a single mutation in the target sequence can result in a large emission wavelength shift [103].…”
Section: Hybridization Activated Fluorescence Our Understanding On Tmentioning
confidence: 99%
“…In a follow-up work, the authors further optimized the DNA sequences and demonstrated that a single mutation in the target sequence can result in a large emission wavelength shift [103].…”
Section: Hybridization Activated Fluorescence Our Understanding On Tmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] Amongst these stabilizers, DNA is very attractive due to its excellent programmability, stability and cost-effectiveness. [26][27][28][29][30] Taking advantage of the strong binding interaction between cytosine and Ag + , a wide range of emission colors are obtained by using various cytosine-rich DNA sequences, [12][13][14][15][16][17]31,32 where NaBH4 has been the exclusively used reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] On the practical side, by rational incorporation of DNA aptamers, the fluorescence signaling of AgNCs has been successfully coupled with the molecular recognition property of DNA to design biosensors and smart imaging probes. [24][25][26][27][28][29][30][31][32][33][34][35][36] An interesting and useful discovery is that the fluorescence of many NCs is strongly quenched by Hg 2+ , allowing its detection at low nM and even sub-nM concentrations. 20,[37][38][39][40][41][42] Despite its importance in analytical chemistry, our fundamental understanding of NCs is still quite limited.…”
Section: Introductionmentioning
confidence: 99%